Women and legal pluralism: a study among hmars of Manipur - Buongpui, Ruth Lalsiemsang (My University, 2016)
The study attempts to understand women’s lives in the context of existing legal pluralism among Hmars. It attempts to look at the ways in which different legal orders deal with issues related to Hmar women, and the negotiations, if any, that Hmar women make through such legal pluralism. Data for the study was garnered through feminist ethnography conducted for two years at intervals in Rengkai, Thenmuol, Ngurte, and Langza villages of Churachandpur District, Manipur. Interviews, case studies, observation, informal interaction, and participant observation at church meetings were used as tools for data collection during ethnography. Besides informal conversations, interviews were conducted with 89 respondents. 57 male respondents and 32 female respondents were interviewed. 32 cases solved through customary law were collected from Hmar community elders and members. 7 state court cases were also collected from Family Court, Lamphel, Imphal, for the period 1993–2013. For archival research, state and private archives were accessed to collect documents related to customary laws in Manipur. Content analysis of church manuals and records was also conducted.
Ray, Sawmya
Keywords: HUMANITIES AND SOCIAL SCIENCES